Determinan Keterlibatan Kerja: Peran Dari Penilaian Kinerja, Perilaku Kepemimpinan dan Perilaku Inovatif - Rahayu Mardikaningsih; Didit Darmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study intends to analyze and determine the determinants of job attachment based on the role of performance appraisal, leadership behavior and innovative behavior. A quantitative approach is used in this research and this descriptive research will collect various information to test hypotheses. The number of samples taken using purposive sampling technique, which is a sampling technique based on certain considerations. The basis of consideration used in determining the number of samples is permanent employees. Based on these considerations, the sample taken was 85 employees. The data collected will be identified with the help of the SPSS version 26 application and the analysis tool used is multiple linear regression analysis. This study concludes that work engagement is significantly influenced by performance appraisal, leadership behavior and innovative behavior. Through a deeper understanding of how work engagement, performance appraisal, leadership behavior and innovative behavior are interrelated, it is hoped that organizations can take strategic steps to improve employee work engagement, and ultimately improve overall performance. This research has the potential to provide valuable insights for human resource practitioners, managers and other stakeholders interested in optimizing their organizational effectiveness